Targeted Green Recovery Measures in a Post-COVID-19 World Enable the Energy Transition - Dafnomilis, Ioannis; Chen, Hsing-Hsuan; den Elzen, Michel; Fragkos, Panagiotis; Chewpreecha, Unnada; van Soest, Heleen; Fragkiadakis, Kostas; Karkatsoulis, Panagiotis; Paroussos, Leonidas; de Boer, Harmen-Sytze; Daioglou, Vassilis; Edelenbosch, Oreane; et al. (Frontiers in Climate, 2022)
Despite the significant volume of fiscal recovery measures announced by countries to deal with the COVID-19 crisis, most recovery plans allocate a low percentage to green recovery. We present scenarios exploring the long-term impact of the COVID-19 crisis and develop a Green Recovery scenario using three global models to analyze the impact of a low-carbon focused stimulus. The results show that a Green Recovery scenario, with 1% of global GDP in fiscal support directed to mitigation measures for three years, could reduce global CO2 emissions by 10.5−15.5% below pre-COVID projections by 2030, closing 8-11.5% of the emissions gap with cost-optimal 2oC pathways. The share of renewables in global electricity generation is projected to reach 45% in 2030, the uptake of electric vehicles would be accelerated, and energy efficiency in the buildings and industry sector would improve. However, such a temporary investment should be reinforced with sustained climate policies after 2023 to put the world on a 2oC pathway by mid-century.